2022
DOI: 10.1007/s12325-022-02182-6
|View full text |Cite
|
Sign up to set email alerts
|

It is Time to Replace Large Drains with Small Ones After Fixation of Rib Fractures: A Prospective Observational Study

Abstract: Introduction Large-bore chest tubes are usually applied after thoracic surgery. Recently, small-bore tubes have been increasingly considered owing to the extensive use of video-assisted thoracoscopic surgery (VATS). This study assessed the differences in outcomes between large-bore and small-caliber drainage tubes in patients undergoing surgical stabilization of rib fractures (SSRF) with VATS. Methods Overall, 131 patients undergoing SSRF with VATS were prospectively en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…They conducted an observational study and concluded that the length of hospital stay was significantly less in patients with small chest tubes than those with large tubes. 18 We did not compare hospital stays. However, obstruction, dislodgment, and infection rates were not statistically significantly different in patients with large or small chest tubes.…”
Section: Discussionmentioning
confidence: 99%
“…They conducted an observational study and concluded that the length of hospital stay was significantly less in patients with small chest tubes than those with large tubes. 18 We did not compare hospital stays. However, obstruction, dislodgment, and infection rates were not statistically significantly different in patients with large or small chest tubes.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, a large-bore chest tube, such as a 28-Fr or 32-Fr tube, is inserted into the chest wall at the proper depth after pneumonectomy (usually 4–5 cm) and clipped and opened intermittently according to the position of the trachea and mediastinum in order to maintain the pressure balance of the thorax [ 3 , 4 ]. Recently, small-hole drainage has been increasingly considered owing to the extensive use of VATS and ERAS [ 5 , 6 ]. We have therefore modified our chest tube management protocol from traditional drainage to a protocol combining one 8.5-Fr pigtail catheter with continuous open gravity drainage, starting in May 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, large-bore chest tube such as 28-Fr or 32-Fr tube is inserted into the chest wall in proper depth after pneumonectomy (usually 4-5 cm) and clipped and opened intermittently according to the position of trachea and mediastinum in order to maintain the pressure balance of the thorax [3][4]. Recently, small holes drainage has been increasingly considered owing to the extensive use of VATS and ERAS [5][6]. We have therefore modi ed our chest tube management protocol from traditional drainage to a protocol combining one 8.5-Fr pigtail catheter with continuous open gravity drainage since May 2016.…”
Section: Introductionmentioning
confidence: 99%